A high-riding brachiocephalic artery: a unique diagnostic dilemma - Ankle, Nitin R.; Rai, Akash; Mehta, Ayushi; Paladugu, Tejaswini (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
We present a case of the A high-riding brachiocephalic artery, a rare variant of neck vessels. It is clinically and surgically important, as unknowingly may lead to severe life-threatening complications. A 67-year-old male, presented with throat pain, dysphagia, heartburn with belching for 4-5 months. He was diagnosed with High riding brachiocephalic on further evaluation with USG neck which was reported as, superiorly placed right brachiocephalic artery noted in the suprasternal notch with maximum diameter 1.6 cm. Asymptomatic nature conservative line of management was followed and on follow up, patient had improvement in the symptoms.